Assessment of methods for predicting the effects of PTEN and TPMT protein variants. Issue 9 (3rd July 2019) - Pejaver, Vikas; Babbi, Giulia; Casadio, Rita; Folkman, Lukas; Katsonis, Panagiotis; Kundu, Kunal; Lichtarge, Olivier; Martelli, Pier Luigi; Miller, Maximilian; Moult, John; Pal, Lipika R.; Savojardo, Castrense; et al.
Abstract: Thermodynamic stability is a fundamental property shared by all proteins. Changes in stability due to mutation are a widespread molecular mechanism in genetic diseases. Methods for the prediction of mutation‐induced stability change have typically been developed and evaluated on incomplete and/or biased data sets. As part of the Critical Assessment of Genome Interpretation, we explored the utility of high‐throughput variant stability profiling (VSP) assay data as an alternative for the assessment of computational methods and evaluated state‐of‐the‐art predictors against over 7, 000 nonsynonymous variants from two proteins. We found that predictions were modestly correlated with actual experimental values. Predictors fared better when evaluated as classifiers of extreme stability effects. While different methods emerging as top performers depending on the metric, it is nontrivial to draw conclusions on their adoption or improvement. Our analyses revealed that only 16% of all variants in VSP assays could be confidently defined as stability‐affecting. Furthermore, it is unclear as to what extent VSP abundance scores were reasonable proxies for the stability‐related quantities that participating methods were designed to predict. Overall, our observations underscore the need for clearly defined objectives when developing and using both computational and experimental methods in the context of measuring variant impact.